2015
DOI: 10.1016/j.vaccine.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, direct costs and duration of hospitalization of patients hospitalized with community acquired pneumonia: A nationwide retrospective claims database analysis

Abstract: There is a large variation in terms of incidence, disease burden and costs across different age groups and the treatment setting. Effective interventions, targeted at older adults, to prevent pneumonia could reduce the (financial) burden due to pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
4
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 25 publications
4
65
4
2
Order By: Relevance
“…Another nationwide ICD-based cost analysis by Rozenbaum et al [19] reported medium costs of CAP of €6060 and €5937 in those 65–74 and 75–84 years of age, respectively, which is also lower than the medium costs for these age cohorts in the current study (€8674 and €8770, respectively). The study by Rozenbaum et al was based on reimbursement of hospital expenses, as regulated by Diagnosis Related Groups (in Dutch: Diagnose BehandelCombinatie or DBC).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Another nationwide ICD-based cost analysis by Rozenbaum et al [19] reported medium costs of CAP of €6060 and €5937 in those 65–74 and 75–84 years of age, respectively, which is also lower than the medium costs for these age cohorts in the current study (€8674 and €8770, respectively). The study by Rozenbaum et al was based on reimbursement of hospital expenses, as regulated by Diagnosis Related Groups (in Dutch: Diagnose BehandelCombinatie or DBC).…”
Section: Discussioncontrasting
confidence: 63%
“…In Western countries like the Netherlands, new healthcare interventions will be evaluated for their costs and effects and detailed cost estimates are indispensable in this process. However, most larger studies describing CAP costs were conducted retrospectively and based on insurance claims with limited clinical information [4, 1419]. The few prospective studies on CAP hospitalization costs covered relative small cohorts only [2022].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is clearly higher in older adults. Recent published estimates from others countries include 130.5 per 10 000 adults aged over 65 years in Malaysia, 25 172.4 cases per 10 000 for adults aged 85 and over in the Netherlands, 26 and 29.6 per 10 000 for all ages and 76.5 for adults aged 65 and over in Germany. 27 …”
Section: Introductionmentioning
confidence: 99%
“…In the United States, it is estimated that there are around 5.2 million adult patients with CAP, and the majority of these individuals are above 65 years old (4.200 out of every 100.000 people) [8]. In the Netherlands, 45% of patients with CAP are above 65 years old [9]. Risk factors for CAP include old age and comorbidity.…”
Section: Resultsmentioning
confidence: 99%